K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 10 2017

\(\left(2x+3\right)^2+\left(2x-3\right)^2-2\left(2x+3\right)\left(2x-3\right)\)

\(=\left(2x+3-2x+3\right)^2\)

\(=9^2\)

\(=81\)

29 tháng 10 2017

\(\left(2x+3\right)^2+\left(2x-3\right)^2-2\left(2x+3\right)\left(2x-3\right)\)

\(=\left(2x+3\right)^2-2\left(2x+3\right)\left(2x-3\right)+\left(2x-3\right)^2\)

\(=\left(2x+3-2x+3\right)^2\)

\(=6^2=36\)

1 tháng 5 2018

a \(2x+2>4\\ \Leftrightarrow2\left(x+1\right)>4\\ \Leftrightarrow x+1>2\\ \Leftrightarrow x>1\)

b \(3x+2>-5\\ \Leftrightarrow3x>-7\\ \Leftrightarrow x>\dfrac{-7}{3}\)

c \(10-2x>2\\ \Leftrightarrow2\left(5-x\right)>2\\ \Leftrightarrow5-x>1\\ \Leftrightarrow-x>-4\\ \Leftrightarrow x< 4\)

d \(1-2x< 3\\ \Leftrightarrow-2x< 2\\ \Leftrightarrow2x>2\\ \Leftrightarrow x>1\)

4 tháng 5 2018

a)2x+2>4

<=> 2x>4-2

<=>2x>2

<=>x>1

Vậy...

b)3x+2>-5

<=>3x>-5-2

<=>3x>-7

<=>x>\(\dfrac{-7}{3}\)

Vậy...

c)10-2x>2

<=>-2x>-10+2

<=>-2x>-8

<=>x<4

Vậy...

d)1-2x<3

<=>-2x<3-1

<=>-2x<2

<=>x>-1

Vậy...

e)10x+3-5\(\le\)14x+12

<=>10x-2\(\le\)14x+12

<=>10x-14x\(\le\)2+12

<=>-4x\(\le\)14

<=>x\(\ge\)\(\dfrac{-7}{2}\)

Vậy...

f)(3x-1)<2x+4

<=> 3x-2x<1+4

<=>x<5

Vậy...

NV
7 tháng 9 2020

a/

\(\Leftrightarrow x-2x^2+2x^2-3x-4x+6=0\)

\(\Leftrightarrow-6x+6=0\)

\(\Leftrightarrow x=1\)

b/

\(\Leftrightarrow2x^2-4x-2x^2-6x=0\)

\(\Leftrightarrow-10x=0\)

\(\Leftrightarrow x=0\)

c/

\(\Leftrightarrow\left(2x+3\right)\left(2x+3+x-3\right)=0\)

\(\Leftrightarrow3x\left(2x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-\frac{3}{2}\end{matrix}\right.\)

NV
7 tháng 9 2020

c/

\(\Leftrightarrow\left(x^2-2xy+y^2\right)+\left(9y^2+30y+25\right)=0\)

\(\Leftrightarrow\left(x-y\right)^2+\left(3y+5\right)^2=0\)

\(\Leftrightarrow\left\{{}\begin{matrix}x-y=0\\3x+5=0\end{matrix}\right.\)

\(\Leftrightarrow x=y=-\frac{5}{3}\)

d/

\(\Leftrightarrow4x^2-4x+1+4x^2+4x+1-2\left(4x^2-2x-2\right)+x=12\)

\(\Leftrightarrow8x^2+x+2-8x^2+4x+4=12\)

\(\Leftrightarrow5x=6\)

\(\Leftrightarrow x=\frac{6}{5}\)

4 tháng 11 2017

(x3 - 9x2 + 27x - 27) - (8x3 + 1) - (x3 + 6x2 + 12x + 8) + (2x - 3)3 + 3.2x.3.(2x - 3) = 0

x3 - 9x2 + 27x - 27 - 8x3 - 1 - x3 - 6x2 - 12x - 8 + (2x)3 - 33 = 0

-15x2 + 15x - 63 = 0

8 tháng 4 2020

\(\left(x-1\right)^2-\left(x+1\right)^2=2\left(x+3\right)\)

\(\Leftrightarrow\left(x-1+x+1\right)\left(x-1-x-1\right)=2\left(x+3\right)\)

\(\Leftrightarrow2x\left(-2\right)=2\left(x+3\right)\)

\(\Leftrightarrow-4x=2x+6\)

\(\Leftrightarrow-6x=6\)

\(\Leftrightarrow x=-1\)
2) \(\left(2x-1\right)^2-\left(2x+1\right)^2=4\left(x-3\right)\)

\(\Leftrightarrow\left(2x-1+2x+1\right)\left(2x-1-2x-1\right)-4\left(x-3\right)=0\)

\(\Leftrightarrow4x\left(-2\right)-4x+12=0\)

\(\Leftrightarrow-12x=-12\)

\(\Leftrightarrow x=1\)

3)\(\left(2x+3\right)^2-\left(2x+3\right)\left(2x-4\right)+\left(x-2\right)^2=0\)

\(\Leftrightarrow\left(2x+3\right)\left(2x+3-2x+4\right)+\left(x^2-4x+4\right)=0\)

\(\Leftrightarrow7\left(2x+3\right)+x^2-4x+4=0\)

\(\Leftrightarrow x^2+10x+25=0\)

\(\Leftrightarrow\left(x+5\right)^2=0\)

\(\Leftrightarrow x=-5\)

4) \(8x^3-\left(x+1\right)^3=3x-3\)

\(\Leftrightarrow8x^3-\left(x^3+3x+3x^2+1\right)-3x+3=0\)

\(\Leftrightarrow7x^3-3x^2-6x+2=0\)

\(\Leftrightarrow\left(x-1\right)\left(7x^2+4x-2\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\frac{-2+3\sqrt{2}}{7}\\x=\frac{-2-3\sqrt{2}}{7}\end{matrix}\right.\)

5)\(\left(3x-2\right)\left(9x^2+6x+4\right)-\left(3x-1\right)\left(9x^2-3x+1\right)=x-4\)

\(\Leftrightarrow\left(3x\right)^3-2^3-\left(\left(3x\right)^3-1^3\right)=x-4\)

\(\Leftrightarrow27x^3-8-\left(27x^3-1\right)=x-4\)

\(\Leftrightarrow-7=x-4\)

\(\Leftrightarrow x=-3\)

13 tháng 4 2020

 \(24x-4\left(2x-\frac{3}{4}\right)-4\left(3+\frac{2x}{2}\right)=36-3\left(x-\frac{3}{2}\right)-3\left(3-\frac{2x}{3}\right)\)

Đề như này đúng không bạn

22 tháng 8 2017

2x^2-6x-4x^2+9=7x-2x^2-17

9-6x-2x^2=7x-2x^2-17

9+17=7x+6x

13x=26

x=2

\(\Leftrightarrow2x^2-6x-4x^2+9=7x-2x^2-17\)

\(\Leftrightarrow13x=26\)

\(\Leftrightarrow x=2\)